The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nano11081989
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviors of Si/CNT Core/Shell Nanocomposites under Tension: A Molecular Dynamics Analysis

Abstract: The silicon/carbon nanotube (core/shell) nanocomposite electrode model is one of the most promising solutions to the problem of electrode pulverization in lithium-ion batteries. The purpose of this study is to analyze the mechanical behaviors of silicon/carbon nanotube nanocomposites via molecular dynamics computations. Fracture behaviors of the silicon/carbon nanotube nanocomposites subjected to tension were compared with those of pure silicon nanowires. Effective Young’s modulus values of the silicon/carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The most promising part occurs at low Young'modulus (E < 5 GPa), where some part of the swelling seems absorbed by the softness of particles, presenting an eventual way to limit the breathing by reducing the particles stiffness. Nevertheless, in practice, the material used for anode is located at much higher range of Young's modulus (E > 5 GPa, 73,74 colored rectangle in Fig. 6b), where the system rigidity becomes such that little breathing changes occurs.…”
Section: Resultsmentioning
confidence: 99%
“…The most promising part occurs at low Young'modulus (E < 5 GPa), where some part of the swelling seems absorbed by the softness of particles, presenting an eventual way to limit the breathing by reducing the particles stiffness. Nevertheless, in practice, the material used for anode is located at much higher range of Young's modulus (E > 5 GPa, 73,74 colored rectangle in Fig. 6b), where the system rigidity becomes such that little breathing changes occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon generally exhibits brittle properties, but it has been confirmed that silicon nanowires of a certain size or less cause ductile transition [ 9 ]. Additionally, it was also confirmed that the ductile transition section expanded further when the silicon nanowire was wrapped by CNT [ 10 ]. Based on these results, an atomistic simulation is a useful tool for comprehensively analyzing the nonlinear behavior of nanomaterials.…”
Section: Introductionmentioning
confidence: 87%
“…For small structures on the scale of nanometers, the intermolecular van der Waals (vdW) interaction can play a leading role in some cases [1]. Since their discovery, carbon nanotubes (CNTs) have shown great application prospects in various fields with their excellent physical and mechanical properties [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%